A Modular Reconfigurable Architecture for Asymmetric and Symmetric-key Cryptographic Algorithms - Zaidi, Ali Mustafa (2007)
It is widely recognized that security issues will play a crucial role in the majority of future computer and communication systems. Cryptographic algorithms are the central tools for achieving system security. Numerous such algorithms have been devised, and many have found popularity in different domains. High throughput and low-cost implementation of these algorithms is critical for achieving both high security and high-speed processing in an increasingly digital global economy. Conventional methods for implementing ciphers are unable to provide all three crucial characteristics in a single solution: high throughput, low-cost, and cipher-agility. This thesis develops a reconfigurable architecture capable of implementing most symmetric-key as well as asymmetric-key ciphers. The reconfigurable nature of the architecture provides flexibility equivalent to software implementations, with the low-cost and throughput figures approaching ASIC implementations of these ciphers. Detailed discussions of the development of this architecture, along with the top-level design and interconnection scheme, have been provided. The individual components developed have been synthesized on a standard-cell library to provide an estimate of the area/performance characteristics of the design. Preliminary results show throughput values equivalent to FPGA based implementations for most of the tested ciphers, and approaching ASIC based implementations. Keywords: Reconfigurable Computing, Cryptography, Symmetric-Key, Asymmetric-Key, Domain-specific Reconfigurable Architectures